Studi Tentang Hubungan Antara Jumlah Modal dengan Jumlah SHU Di KPN “Keluarga Sehati” SMKN - 2 Palangkaraya Tahun 2008-2013 - Iin Nurbudiyani (Anterior Jurnal, 2014)
This study aimed to find out: (1) the increase of capital in KPN Keluarga Sehati SMKN-2 Palangkaraya 2008-2013; (2) The increase of SHU in KPN Keluarga Sehati SMKN-2 Palangkaraya 2008-2013; (3) is there any correlation between capital enhancement to SHU in KPN Keluarga Sehati SMKN-2 Palangkaraya 2008-2013. The population were all committee members and staffs. The data were data primer (transaction posts in final income which has correlation to capital enhancement and SHU). Data secondary data (the committee report in the final period income which has correlation to capital enhancement and SHU. This study used interview and documentation. Data analysis used two steps: calculation and finishing technique of data analysis used product moment Karl Pearson, and to analyze the correlation degree and to compare the correlation gained or identified “r”. if “r” is bigger than r critic it is significant. The significant score automatically reject Ho accepted Hi, based on the significant level 5%. Involve in “r” product moment. the result described as following: (1) the capital enhancement in KPN Keluarga Sehati SMKN-2 Palangkaraya in 2008-2013 increased in each year; (2) the enhancement income in KPN Keluarga Sehati SMKN-2 Palangkaraya in 2008-2013 increased and decreased each year; (3) the correlation between capital enhancement and income enhancement in KPN Keluaraga sehati SMKN-2 Palangkaraya has no correlation, it caused of the committee prior is to welfare members than profit.